Students’ Learning Motivation in Online Practicum Courses during COVID-19 Pandemic: A Case of Walisongo State Islamic University - Niam, Muhammad Yusrun; Fuadiyah, Ma’lumatul; Wijayanti, Erna (Jurnal Pendidikan MIPA, 2020)
This research aims to identify student learning motivation in online practicum courses during the COVID-19 pandemic. This study used a quantitative survey method toward 117 biology students at the Walisongo State Islamic University. Data were collected using five-point Likert scale questionnaire. The data show that students learning motivation is in good criteria (75.47%). The percentage breakdown and criteria for each indicator are as follows: concentration 77.9% (good), curiosity 81.06% (very good), enthusiasm 66.67% (good), independence 82.64% (very good) ), readiness 77.78% (good), enthusiasm 66.7% (good), never give up 72.82% (good), and confidence 78.21% (good). This study's result can be used as an evaluation material for designing effective online learning during the COVID-19 pandemic. Keywords: learning motivation, online practicum courses, COVID-19 pandemic.  DOI: http://dx.doi.org/10.23960/jpmipa/v21i2.pp120-131